Removal of foreign bodies in the upper gastrointestinal tract in adults: European Society of Gastrointestinal Endoscopy (ESGE) Clinical Guideline - Birk, Michael; Bauerfeind, Peter; Deprez, Pierre H.; Häfner, Michael; Hartmann, Dirk; Hassan, Cesare; Hucl, Tomas; Lesur, Gilles; Aabakken, Lars; Meining, Alexander (Endoscopy, 2016)
This Guideline is an official statement of the European Society of Gastrointestinal Endoscopy (ESGE). It addresses the removal of foreign bodies in the upper gastrointestinal tract in adults.RecommendationsNonendoscopic measures1 ESGE recommends diagnostic evaluation based on the patient’s history and symptoms. ESGE recommends a physical examination focused on the patient’s general condition and to assess signs of any complications (strong recommendation, low quality evidence).2 ESGE does not recommend radiological evaluation for patients with nonbony food bolus impaction without complications. We recommend plain radiography to assess the presence, location, size, configuration, and number of ingested foreign bodies if ingestion of radiopaque objects is suspected or type of object is unknown (strong recommendation, low quality evidence).3 ESGE recommends computed tomography (CT) scan in all patients with suspected perforation or other complication that may require surgery (strong recommendation, low quality evidence).4 ESGE does not recommend barium swallow, because of the risk of aspiration and worsening of the endoscopic visualization (strong recommendation, low quality evidence).5 ESGE recommends clinical observation without the need for endoscopic removal for management of asymptomatic patients with ingestion of blunt and small objects (except batteries and magnets). If feasible, outpatient management is appropriate (strong recommendation, low quality evidence).6 ESGE recommends close observation in asymptomatic individuals who have concealed packets of drugs by swallowing (“body packing”). We recommend against endoscopic retrieval. We recommend surgical referral in cases of suspected packet rupture, failure of packets to progress, or intestinal obstruction (strong recommendation, low quality evidence).Endoscopic measures7 ESGE recommends emergent (preferably within 2 hours, but at the latest within 6 hours) therapeutic esophagogastroduodenoscopy for foreign bodies inducing complete esophageal obstruction, and for sharp-pointed objects or batteries in the esophagus. We recommend urgent (within 24 hours) therapeutic esophagogastroduodenoscopy for other esophageal foreign bodies without complete obstruction (strong recommendation, low quality evidence).8 ESGE suggests treatment of food bolus impaction in the esophagus by gently pushing the bolus into the stomach. If this procedure is not successful, retrieval should be considered (weak recommendation, low quality evidence). The effectiveness of medical treatment of esophageal food bolus impaction is debated. It is therefore recommended, that medical treatment should not delay endoscopy (strong recommendation, low quality evidence).9 In cases of food bolus impaction, ESGE recommends a diagnostic work-up for potential underlying disease, including histological evaluation, in addition to therapeutic endoscopy (strong recommendation, low quality evidence).10 ESGE recommends urgent (within 24 hours) therapeutic esophagogastroduodenoscopy for foreign bodies in the stomach such as sharp-pointed objects, magnets, batteries and large/long objects. We suggest nonurgent (within 72 hours) therapeutic esophagogastroduodenoscopy for medium-sized blunt foreign bodies in the stomach (strong recommendation, low quality evidence).11 ESGE recommends the use of a protective device in order to avoid esophagogastric/pharyngeal damage and aspiration during endoscopic extraction of sharp-pointed foreign bodies. Endotracheal intubation should be considered in the case of high risk of aspiration (strong recommendation, low quality evidence).12 ESGE suggests the use of suitable extraction devices according to the type and location of the ingested foreign body (weak recommendation, low quality evidence).13 After successful and uncomplicated endoscopic removal of ingested foreign bodies, ESGE suggests that the patient may be discharged. If foreign bodies are not or cannot be removed, a case-by-case approach depending on the size and type of the foreign body is suggested (weak recommendation, low quality evidence).